СУТНІСНІ АСПЕКТИ РОЗВИТКУ СУВЕРЕННИХ МОРАЛЬНИХ ЦІННОСТЕЙ ОСОБИСТОСТІ - Педоренко, Валентина (Психологія і суспільство, 2017)
У статті, на основі детального аналізу досліджень представників різних напрямів психології, аргументована можливість виділення та існування суверенних моральних цінностей особистості як стійких, самісно значущих, смисложиттєвих моральних утворень (взірці, поняття, установки), що дають змогу самій людині оцінювати перебіг власного життя та повсякдення інших людей. Водночас розкрито зміст цих цінностей, проаналізовано наукові дослідження з проблеми їх формування у періоді юності, обґрунтована їх значущість для майбутнього психолога в контексті його професійної підготовки. Крім того, виокремлено низку функцій СМЦ: трансцендентна, відображувальна, адаптивна, мобілізуюча, захисна, експресивна, пізнавальна, гармонізаційна та розкрито їх психологічний зміст. A nuanced analysis of a large number of researches between different areas of psychology in the article are made and on the basis the sovereign moral values as steady, personally meaningful, life-purpose moral formation (samples, concepts, installations) that allows a person toself-concept their own life and the lives of others are separated.The importance of sovereign moral values for the personality in general and for future psychologists in the context of the exercise of their professional training: contribute to the formation of the existential confidence (freedom ofmeaningfulness, values oftheir own existence), creative attitude to one’s own life, criticality to ideological influences, personal responsibility is analyzed.Based on the analysis of scientific papers of D. Leontyev, V. Frankl, M. Savchyn, S. Nartova-Bochaver and others, the features of sovereign moral values: the transcendental, displayable, adaptive, protective, physical, expressive, cognitive, harmonization are highlighted and the content is revealed.Analysis of the significant amount of scientific research on the problems offormation the value system in the period of youth gave the possibility to separate the types of sovereign moral values of the psychologist: responsibility for the life of another person; sensitivity, tolerance, kindness to the client; the ability to choose morally grounded methods and methods of correction; ability to defend their own honor, dignity, clearly understand their civil rights, freedom and responsibilities; readiness to protect its own independent moral position, beliefs, ideas; the ability to understand the meaning of professional work in the context of life; ability to act honestly, independent of the external circumstances etc.